1999
DOI: 10.1136/vr.144.15.405
|View full text |Cite
|
Sign up to set email alerts
|

A blinded, placebo‐controlled study of the efficacy of borage seed oil and fish oil in the management of canine atopy

Abstract: Twenty-one dogs with atopy were entered into a blinded, placebo-controlled study lasting eight weeks. They were randomly divided into three groups and were all given supplementary oils orally once daily. The dogs in groups A and B were given borage seed oil and fish oil in combination (Viacutan; Boehringer Ingelheim Vetmedica) to provide 176 mg/kg or 88 mg/kg borage seed oil respectively. The dogs in group C were given 204 mg/kg olive oil as a placebo. They were all re-examined after four and eight weeks and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 19 publications
2
38
1
Order By: Relevance
“…This finding is in accordance with a previous open study, which reported that supplementation with omega‐6 and omega‐3 dietary fatty acids reduced the prednisolone requirements in eight of 11 dogs with atopic dermatitis 15 . The beneficial effect of borage seed oil and fish oil supplementation in the treatment of canine atopic dermatitis has recently been reported by Harvey 35 . Harvey gave the fatty acid supplement as the sole anti‐inflammatory treatment, and in considerably higher concentrations than those used in the present study 35 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in accordance with a previous open study, which reported that supplementation with omega‐6 and omega‐3 dietary fatty acids reduced the prednisolone requirements in eight of 11 dogs with atopic dermatitis 15 . The beneficial effect of borage seed oil and fish oil supplementation in the treatment of canine atopic dermatitis has recently been reported by Harvey 35 . Harvey gave the fatty acid supplement as the sole anti‐inflammatory treatment, and in considerably higher concentrations than those used in the present study 35 .…”
Section: Discussionsupporting
confidence: 92%
“…The beneficial effect of borage seed oil and fish oil supplementation in the treatment of canine atopic dermatitis has recently been reported by Harvey 35 . Harvey gave the fatty acid supplement as the sole anti‐inflammatory treatment, and in considerably higher concentrations than those used in the present study 35 . Neither of these earlier studies included a control for the dogs’ regular diet.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, an increase in patients with canine atopic dermatitis from 7% in 1981 2 to 12% in 1990 1 has been observed in North‐east America. A variety of drugs such as glucocorticoids, 23 cyclosporin, 20 antihistamines, 24 fatty acids 21,25,26 or combinations thereof 27–29 have been used for the treatment of atopic dermatitis: a comprehensive review has recently been published 4 . These treatments are symptomatic and evidence of long‐lasting remission after cessation of therapy has been scarce 30 …”
Section: Discussionmentioning
confidence: 99%
“…A few studies in dogs showed good success in the therapy of the CAD with diets rich in PUFA. Obviously the n6‐ to n3‐ratio has an influence on the therapy success (Bond and Lloyd, 1992; Scarff and Lloyd, 1992; Logas and Kunkle, 1994; Sture and Lloyd, 1995; Scott et al., 1997; Harvey, 1999). Furthermore, it has been shown in studies with healthy dogs that fatty acids influence pro‐inflammatory lipid mediators (Vaughn et al., 1994, Kearns et al., 1999; Byrne et al., 2000).…”
Section: Discussionmentioning
confidence: 99%